Debugger Canvas: Industrial Experience with the Code Bubbles Paradigm - Bragdon, Andrew; Rowan, Kael; Jacobsen, Jens; DeLine, Robert; DeLIne, Robert (International Conference on Software Engineering, 2012)
At ICSE 2010, the Code Bubbles team from Brown University and the Code Canvas team from Microsoft Research presented similar ideas for new user experiences for an integrated development environment. Since then, the two teams formed a collaboration, along with the Microsoft Visual Studio team, to release Debugger Canvas, an industrial version of the Code Bubbles paradigm. With Debugger Canvas, a programmer debugs her code as a collection of code bubbles, annotated with call paths and variable values, on a twodimensional pan-and-zoom surface. In this experience report, we describe new user interface ideas, describe the rationale behind our design choices, evaluate the performance overhead of the new design, and provide user feedback based on lab participants, post-release usage data, and a user survey and interviews. We conclude that the code bubbles paradigm does scale to existing customer code bases, is best implemented as a mode in the existing user experience rather than a replacement, and is most useful when the user has a long or complex call paths, a large or unfamiliar code base, or complex control patterns, like factories or dynamic linking.